Quantifying trade secret theft: Policy implications - Dan Ciuriak; Marija Ptashkina (Centre for International Governance Innovation (CIGI), 2021)
In the modern data-driven economy, trade secrets are becoming a more important part of firms' intellectual property (IP) strategies. For their part, governments worldwide have been introducing new legislation to broaden and toughen the protection for trade secrets, citing estimates of the cost of trade secret theft in the order of one-three percent of the GDP of advanced countries or in the order of hundreds of billions of dollars annually. This paper reviews the rise of trade secrets from relative obscurity to a major issue in international economic governance; analyzes the obligations on firms to establish protected knowledge as a trade secret; considers the evidence on the leakage of trade secrets in terms of frequency, scale and means (for example, cybertheft and intercorporate movements of personnel); and examines the robustness of existing estimates of the value of trade secret theft. Given that IP protection is a two-edged sword, the paper also examines the risks of collateral damage to the vitality of the modern innovation-intensive economy of more expansive protections and harsher criminal sanctions. While the evolution of the economy necessitates modernization of IP protection to address the modern context for trade secret theft, the paper concludes that the available evidence does not support the expansive claims of trade secret theft that have fuelled international tensions and, by extension, points to reform efforts that focus on updating and clarifying trade secrets regimes with a balanced perspective on protecting firms' valuable IP while not undermining the dynamism of innovation systems.
Keywords: 330